2020
DOI: 10.1038/s41598-020-71498-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of traumatic spinopelvic instabilities treated with lumbopelvic fixation

Abstract: The aim of this study was to assess the functional outcome after lumbopelvic fixation (LPF) using the SMFA (short musculoskeletal functional assessment) score and discuss the results in the context of the existing literature. The last consecutive 50 patients who underwent a LPF from January 1st 2011 to December 31st 2014 were identified and administered the SMFA-questionnaire. Inclusion criteria were: (1) patient underwent LPF at our institution, (2) complete medical records, (3) minimum follow-up of 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Traumatic lumbopelvic dissociation is an extremely rare injury that accounts for ~1% of all spinal fractures and is always the result of high-energy trauma [ 3 ]. Due to the high energy of these traumatic events, concomitant injuries are extremely common and there are extremely high rates of neurological deficits and infection as seen in our case report [ 10 , 11 , 13 ]. The optimal treatment of these injuries has not been well described and usually depends on surgeon preference as well as ability [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Traumatic lumbopelvic dissociation is an extremely rare injury that accounts for ~1% of all spinal fractures and is always the result of high-energy trauma [ 3 ]. Due to the high energy of these traumatic events, concomitant injuries are extremely common and there are extremely high rates of neurological deficits and infection as seen in our case report [ 10 , 11 , 13 ]. The optimal treatment of these injuries has not been well described and usually depends on surgeon preference as well as ability [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 96%
“…The optimal treatment of these injuries has not been well described and usually depends on surgeon preference as well as ability [ 4 , 7 ]. Despite the findings that function, sacral slope, and subjective feelings of pain all improve, patients treated with lumbopelvic fixation still suffer from some level of impairment at follow-up [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies, with small cohorts, that have reported on the quality of life and functional outcomes of patients after spinopelvic dissociation [ 11 – 13 ]. This indicates that spinopelvic dissociation is a rare injury.…”
Section: Introductionmentioning
confidence: 99%